Tradition und Avantgarde Das Sonett im Expressionismus - Buohler, Hans Peter (Klassische Moderne, 2022)
How much tradition is there in the avant-garde? Is everything that is claimed to be new really new? Literary Expressionism (the most important avant-garde movement of Classical Modernism), which was and still is generally considered to be the epoch of "broken forms", claimed this for itself: after all, artists had revolutionary experiences (such as the First World War) to deal with and often created something new. But not always, and so numerous sonnets can be found in poetry - and thus poems in a form from the 13th century. By showing (thanks to extensive source and archive studies) that this is a poetic mass phenomenon, however, Expressionism is now seen in a different light, revealing new facets in literature between 1905 and 1925. Case studies on the outstanding poets of early expressionism (Georg Heym and Georg Trakl), the period of the First World War (Max Herrmann-Neisse and Paul Zech) and the young Weimar Republic (Anton Schnack and Walter Rheiner) deepen this finding. In addition, the work is highly compatible both intermedially (music and visual arts) and comparatively (the sonnet as a European form of poetry) and also facilitates further literary studies thanks to an extensive appendix of sources.